Financial Analisis Pengaruh Faktor Fundamental dan Teknikal Terhadap Return Saham - Bayu Anggara Silvatika; Marlina Widiyanti (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2018)
This research aims to examine the impact of fundamental and technical factors towards stock returns, and with macroecomoic as moderation variable. The population used in this research is all public companies or issuer listed in Indonesia Stock Exchange from 2008 to 2012. The companies used samples are 23 companies which categorized as LQ-45 that exist from 2008 to 2012 or using Purposive Sampling Method. Analysis of securitas consist of fundamental and technical analysis. In fundamental analysis and technical, analist often uses factors fundamental and technical. Fundamental’s and technical’s factors in Multi-factor Models uses to perform the portfolio with special characteristics. Multi-factor Models are improved from the concept of Arbitrage Pricing Theory (APT). Fundamental factors are consisted Financial Ratio (ROA, DER, EPS, PBV) and macroeconomic (exchange rate, inflations, gdp); than technical factors (trading volume, market capitalization, and previous stock price). Those are independen variables which towards stock return using Panel’s Data then make analysis using Multiple Regressions. This research shows that partially, several fundamental factors (ROA, DER, and EPS) have not significant influence and positif are toward stock return. However, PBV have significant influence and negatif are toward stock return. Several macro economic’s factors (kurs and GDP) have significant influence and positif are toward stock return, but inflation have significant influence at α = 10%. All of technical’s factors (trading volume, market capitalization, and previous stock price) have not significant influence and positif (market capitalization, and previous stock price), negatif (trading volume) are toward stock return.Simultaneously, fundamental’s factors, macro economic, and technical’s factors have significant influence and positif are toward stock return. Managerial implication of this research are the investors can use fundamentals analysis with focus on PBV ratio, emiten must be more attention macro economic factors, especially exchange rate and GDP. Investors in Indonesia Stock Market more like fundamental’s analysis than technical’s analysis, but investor also can use integrated analysis by combine of fundamental and technical’s analysis.